CHARACTERIZATION OF THE NUTRITIONAL COMPOSITION, PH, AND COLOUR ATTRIBUTES OF KING ORANGE (Citrus sinensis) JUICE FROM DIFFERENT CULTIVATION REGIONS IN VIETNAM - Van Loi, Nguyen; Thi Cuong, Vu; Phuong Thao, Bui (HNUE Journal of Science: Journal of Natural Sciences, 2026)
In Vietnam, king oranges are cultivated throughout the country, especially in the Tuyen Quang, Bac Ninh, Phu Tho, Lang Son, Vinh Long, and Dong Thap provinces, occupying large cultivation areas and contributing substantially to national production. Therefore, the objective of this study is to determine the nutritional composition, pH, and colour indexes of king orange juice in different cultivating regions, in order to provide a scientific basis for developing a process for industrial scale bottling and long-term preservation of king orange juice, which is essential and has high scientific and practical significance. The process involved several steps, extracting and collecting the juice from king oranges, then using physicochemical, biochemical, and sensory analysis methods to determine several nutritional indicators, pH levels, and the colour of the king orange juice. The research results showed that the Tuyen Quang king orange juice had higher soluble solids, total sugar content, vitamin C content, vitamin A content, and pH value than other orange juices. Specifically, king orange juice from Tuyen Quang exhibited a soluble solid of content of 10.93 ± 0.9 (oBx), a total sugar content is 10.39 ± 0.8 (g/100mL), a vitamin C content is 14.36 ± 0.4 (μg/100mL), a vitamin A content is 53.16 ± 1.2 (mg/100mL), a protein content is 1.32 ± 0.3 (g/100mL) and a pH value is 4.3 ± 0.2. Among the six king orange juices evaluated, the Tuyen Quang king orange juice had a brighter, more characteristic, and more attractive yellow colour than the other samples. These results suggest that soil conditions, weather, climate, and growing conditions also affect the nutritional components and colour of king orange juice.